2021
DOI: 10.1177/10497323211042869
|View full text |Cite
|
Sign up to set email alerts
|

“Sewing Is Part of Our Tradition”: A Case Study of Sewing as a Strategy for Arts-Based Inquiry in Health Research With Inuit Women

Abstract: In this article, we present a case study of sewing as a strategy for arts-based inquiry in health research, situated within a broader project that highlighted Nunavut Inuit women’s childbirth experiences. Five focus groups were hosted as sewing sessions with pregnant women ( N = 19) in Iqaluit, Nunavut (2017–2018). Women’s reflections on the sessions, and the significance of sewing to Inuit, were integrated with researchers’ critical reflections to examine the value of sewing as a strategy for arts-based inqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Some studies reported that consultations ensured that the research was aligned with community priorities and conducted in a culturally appropriate way 36 70 72 100–103. Two studies reported that the consultations with Inuit organisations and partners ensured that the research is rooted in an Indigenous perspective 104 105…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies reported that consultations ensured that the research was aligned with community priorities and conducted in a culturally appropriate way 36 70 72 100–103. Two studies reported that the consultations with Inuit organisations and partners ensured that the research is rooted in an Indigenous perspective 104 105…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, authors incorporated Inuit cultural practices during the data collection 45 48 105. Two recent studies used traditional craft activities like sewing and seal fur earing in focus groups 45 105.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations